Developing Religious Identity: Assessing the Effects of Aliya Madrasahs on Muslim Students in Bangladesh - M Mahmudulhassan; Muhammad Abuzar (Walidem Institute and Publishing (WIP), 2024)
This study explores the complex function of Aliya Madrasahs in Bangladesh, particularly emphasising how they affect Muslim students' identities and religious practices. The study clarifies the complex roles these institutions play through qualitative methods. Aliya Madrasah offers contemporary and religious education, encouraging academic instruction, spiritual development, moral improvement, and community involvement. The curriculum covers various topics and incorporates modern knowledge with Islamic principles. The research also outlines areas that require improvement, including community participation programs, teacher preparation programs, infrastructural development, and curriculum improvements. Aliya Madrasahs can improve their ability to mould practising Muslims who can navigate both the religious and secular arenas by putting these suggestions into practice. This study provides ideas for future growth and development while highlighting Aliya Madrasah's crucial role in shaping Muslim students' religious identities and practices in Bangladesh.